(untitled) (Вестник КазНУ. Серия Востоковедения, 2017)
Short review of the history of investigating Turkish proverbs and sayings is made in the article. The analysis of proverbs and sayings that are considered to be a treasure of national wisdom enables to reveal stereotypes connected with role and place of men and women in society.